Petechial hemorrhage in mechanical thrombectomy for distal and medium-vessel occlusions: technical considerations and outcomes - Essibayi, Muhammed Amir; Salim, Hamza Adel; Fazzari, Melissa J.; Khatri, Deepak; Baker, Amanda; Musmar, Basel; Adeeb, Nimer; Henninger, Nils; Sundararajan, Sri Hari; Kühn, Anna Luisa; Khalife, Jane; Ghozy, Sherief; et al. (Journal of neurosurgery, 2025)
OBJECTIVE Mechanical thrombectomy (MT) is well established for large-vessel occlusion (LVO) strokes, but its safety in distal and medium-vessel occlusions (DMVOs) requires further investigation. This study analyzed the relationship between procedural approaches, petechial hemorrhage (PetH), and clinical outcomes in DMVO thrombectomy, with particular attention to technical considerations and the complex interplay between tissue injury and hemorrhagic complications. METHODS A retrospective cohort study was conducted on DMVO stroke patients treated with MT at 37 stroke centers worldwide from 2016 to 2024. Patients were categorized based on follow-up imaging into those with or without PetH. Four logistic regression models analyzed the association of PetH with favorable functional outcomes (modified Rankin Scale score ≤ 2) at 90 days, early neurological improvement (≥ 4-point National Institutes of Health Stroke Scale score decrease at 24 hours), all-cause mortality, and independent determinants of PetH. Adjusted odds ratios (aORs), 95% confidence intervals, and p values were reported. RESULTS Of 1428 patients, 439 (30.7%) developed PetH. Factors independently associated with PetH were multiple thrombectomy passes (aOR 1.58, 95% CI 1.21-2.06; p = 0.001), IV thrombolysis (aOR 1.31, 95% CI 1.01-1.69; p = 0.04), and the combined use of a stent retriever with aspiration as the first-line method compared with aspiration alone (aOR 1.66, 95% CI 1.15-2.38; p = 0.007). Conversely, general anesthesia (aOR 0.55, 95% CI 0.40-0.77; p < 0.001), higher Alberta Stroke Program Early CT Scores (aOR 0.76, 95% CI 0.69-0.83; p < 0.001), and successful recanalization (aOR 0.56, 95% CI 0.39-0.80; p = 0.002) were significantly associated with a lower odds of PetH. PetH was associated with a decreased odds of favorable functional outcomes (aOR 0.51, 95% CI 0.36-0.73; p < 0.001), reduced early neurological improvement (aOR 0.59, 95% CI 0.44-0.79; p < 0.001), and increased all-cause mortality (aOR 1.84, 95% CI 1.23-2.76; p < 0.001). CONCLUSIONS PetH is a frequent sequela following MT in DMVO strokes and is associated with poorer outcomes, likely reflecting underlying ischemic injury rather than direct causation. Procedural factors influence PetH risk, suggesting medical treatment as first-line therapy for DMVOs, with MT reserved for refractory cases using less aggressive approaches.
Veröffentlicht: 04. Juli 2025
Gesehen am 20.02.2026